Strategi Marketing Dalam Meningkatkan Produk Tabungan Emas Pada PT Pegadaian Syariah Cabang untung suropati Pasuruan - Sagita Martha Triyani; Saiful Bakhri (CV. ITTC INDONESIA, 2023)
This research aims to answer marketing strategy problems in improving gold savings products at PT. Sharia Pawnshop Untung Suropati Pasuruan Branch. This type of qualitative research uses descriptive analysis methods. Research data collection techniques from field research were obtained through interviews and documentation sourced from library research in the form of reading books. The results of this research indicate that the marketing strategy in increasing gold savings products at PT. Pegadaian Syariah Untung Suropati Pasuruan Branch, provides quite satisfactory information, carries out segmentation in the form of outreach to all levels of society with the target market, carries out literacy (introduction) of gold installment savings products to the community, offices and schools, as well as relating to the marketing mix including product, price, promotion and place. And carry out promotions via social media. The best marketing strategy is literacy (introduction) of gold savings products to the public, so that they are in great demand among housewives (IRT) and non-PNS employees, PKK women.